COVID-19 Pandemic and Physical Exercise: Lessons Learnt for Confined Communities - Ghram, Amine; Bragazzi, Nicola Luigi; Briki, Walid; Jenab, Yaser; Khaled, Mehdi; Haddad, Monoem; Chamari, Karim (Frontiers in Psychology, 2021)
The novel pandemic called coronavirus disease 2019 (COVID-19), as a global public health emergency, seems to be having a major impact on physical activity (PA) behaviors. Specific population including refugees, seek asylums, and prisoners are at high risk of death from the severe acute respiratory syndrome coronavirus 2 (SARS CoV-2). Governments around the world have been implementing preventive health measures, including self-isolation, to mitigate the COVID-19 outbreak. This period is characterized by reduced of lack of movement. During this period of lockdown, PA as immunotherapy and effective strategy to avoid the harmful effects of periods of pandemic and feeling incarcerated, PA could be prescribed to refugees, seek asylums, and prisoners and improving the immunity system. The present article discusses the potential impacts of COVID-19 pandemic on specific population. The importance of performing PA to reduce the harmful effects of COVID-19 pandemic is discussed, and useful recommendations on exercise for the specific population to maintain their level of independence, physical and mental health as well as their wellbeing are provided.